Oreocharis chenzhouensis, a new species of Gesneriaceae from southern Hunan, China - Zhou, Guo-Hui; Tu, Rong-Hui; Liu, Ang; Yu, Xun-Lin (Phytotaxa, 2023)
Oreocharis chenzhouensis, a new species, is described and illustrated from southern Hunan, China. The new species resembles O. burtii and O. sinohenryi in leaf blade shape and indumentum of the plants, but readily differs from the latter two in its leaf blade with a cuneate and usually asymmetric base, abaxially glabrous corolla tube, narrowly triangular calyx lobes, and one or no staminode. Following the IUCN Red List Criteria, O. chenzhouensis is assessed as “Vulnerable”.